Metode persalinan dan hubungannya dengan inisiasi menyusu dini di RSUP Dr. Sardjito Yogyakrta - Sheilla Virarisca; Djaswadi Dasuki; Sulchan Sofoewan (Jurnal Gizi Klinik Indonesia, 2010)
Background: The 2002-2003 IDHS shows that the presentation of breastfeeding within an hour after birth or early initiation in Indonesia is still low (38%). According to some studies, early initiation plays an important role in reducing infant mortality rate, determining the success of exclusive breastfeeding, preventing pre-lactation feeding, creating more intensive bonding between mother and baby. Some earlier studies state that delivery methods are related with early initiation. However, there have been some studies whose results are in contrast with those previous studies.Objective: To study the relationship between delivery methods and early initiation in Dr. Sardjito hospital, Yogyakarta.Method: This was an observational study with a cross-sectional study design through quantitative and qualitative approaches. Samples were postpartum women in Dr. Sardjito hospital as many as 100 respondents. Data were analyzed with univariable analysis using frequency distribution table, bivariable analysis using chi-square, and multivariable analysis using binary regression.Results: The proportion of early initiation of breastfeeding was three times greater in women who gave birth with normal delivery methods than women who gave birth with cesarean section (RR=3.1; 95% CI=1.42-6.89). Another factor that was related with early initiation of breastfeding was the support from health providers (RR=2.3; 95% CI=1.36-3.78). Meanwhile, women’s age, knowledge, parity, economic status, and mother’s disease were insignifcantly related with early initiation.Conclusion: The proportion of early initiation of breastfeeding  was three times greater in women who gave birth with normal delivery methods than women who gave birth with cesarean section. Another factor that was related with early initiation of breastfeeding was the support from health providers. Meanwhile, women’s age, knowledge, parity, economic status, and disease were insignifcantly related with early initiation of breastfeeding.